DNA Barcoding Technology Used to Successfully Sub-Classify a Museum Whale Specimen as Balaenoptera edeni edeni - Ren, Xiaoying; Ma, Xiaolin; Allen, Edward; Fang, Yuan; Wen, Shaoqing (Frontiers in Ecology and Evolution, 2022)
DNA barcoding technology is becoming an increasingly powerful tool in resolving issues of detailed species identification based on morphology, as commonly employed by museums. In the present study, we aimed to identify a stranded Bryde's whale on Hainan Island, China by extracting DNA from a vertebra pre-treated by physical and/or chemical processes. Based on morphological characteristics, this Bryde's whale was initially determined as Balaenoptera edeni. Then, DNA was efficiently extracted using ancient DNA techniques. The mitochondrial gene (COI) phylogenetic analysis further revealed that this museum whale specimen belonged to the sub-species B. e. edeni. This study provides a testable and rapid method for museum species verification, by using ancient DNA extraction methods to compensate the disadvantage of traditional DNA extraction methods that are difficult to extract valid DNA.